Rites and rituals performed at the Ghats of Banganga Tank - Banganga by Ghosh, Ayan (2023)
Early European visitors to Walkeshwar mention the site as a 'Brahmin village'. The ghats surrounding Banganga Tank are maintained by the Gaud Saraswat Brahmin Temple Trust. The materials required for performing ceremonies, like flowers, incense, and coconut, are arranged by hereditary Brahmin priests from diverse communities living at Walkeshwar for many centuries. They conduct a variety of Hindu rituals like thread ceremonies, childbirth, marriages, cremation rites, morning and evening libations, and offerings of pitripujas and shraddh.